DAILY AND SHORT-PERIOD CHANGES DYNAMICS OF THE EARTH’S MAGNETIC FIELD IN THE 24-TH CYCLE OF SOLAR ACTIVITY ACCORDING TO MAGNETIC OBSERVATORY "ODESSA" - Guglya, L. I.; Orlyuk, M. I.; Ryabov, M. I.; Sukharev, A. L.; Orlyuk, I. M. (Одеські астрономічні публікації, 2013)
The Registration of Bx, By, Bz - vector components of the Earth's magnetic field, with a time resolution in 1 second is carried out on magnetic observatory " Odessa". . Results of calculated module of a full vector of magnetic field variations for 2008-2010 are analyzed. "The quasi-daily period" of solar dynamics is determined by wavelet analysis. The daily period and the spectra of shorter duration periods are substracted by digital filtering method. In consequence of the recieved data magnetic storm time specifications are shown.